The Analisis Pendapatan Nasional Indonesia Berdasarkan Berbagai Sektor Lapangan Usaha - Anthony Chang (Politeknik Kutaraja, 2021)
This study was done with the goal to analyze Indonesia’s national income growth based on various industry sectors from the year 2016 to 2020 based on its GDP (Gross Domestic Product). This study utilizes the literature study method with the quantitative data that was collected through official online sources. Based on the study that was conducted, In the year 2019 to 2020 almost all industry sectors in Indonesia experienced a decline on its GDP. Especially in the manufacturing sector, construction sector, transportation sector, and accommodation sector. While there are also a couple of industry sectors that actually experienced growth during this time, such as the information and communication sector as well as the health service and social activities sector. It was found that this phenomenon was caused by the impact of the recent Covid-19 pandemic.